2015
DOI: 10.1177/0161734615595015
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Tissue Evaluation of Atrial Conduction Properties in Patients With Non-alcoholic Fatty-liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in clinical practice, and there is an increasing trend in its prevalence in the general population. Recent studies have demonstrated increased risk of atrial fibrillation (AF) in NAFLD. However, information on the mechanism of increased risk of AF in NAFLD is lacking. Impaired atrial conduction is an important factor in the pathophysiology of AF. We aimed to investigate atrial conduction properties in patients with NAFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 31 publications
(62 reference statements)
0
24
0
Order By: Relevance
“…Non-alcoholic fatty liver disease (NAFLD) without cardiac disease, diabetes, or hypertension: in a population of NAFLD without any clinical diagnosis of cardiac disease, diabetes, hypertension, increased left atrial volume, PWD was significantly higher when compared with controls [30].…”
Section: Normal Limit Values Of P-wave Dispersion (Pwd)mentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) without cardiac disease, diabetes, or hypertension: in a population of NAFLD without any clinical diagnosis of cardiac disease, diabetes, hypertension, increased left atrial volume, PWD was significantly higher when compared with controls [30].…”
Section: Normal Limit Values Of P-wave Dispersion (Pwd)mentioning
confidence: 99%
“…This increased epicardial adipose tissue is associated with sympathovagal imbalances that can predispose to cardiac arrhythmias, such as first degree heart block prolongation and atrial fibrillation. [106][107][108][109][110][111] A prospective cohort study following diabetic patients for 10 years showed that patients with NAFLD developed atrial fibrillation more often than the controls. 112 These findings suggest a potential role for screening and surveillance of atherogenic dyslipidemia in patients with NAFLD.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Additionally, patients with NAFLD have alterations in cardiac structure which may predispose to AF development . A number of studies have reported increased left atrial volume and size, left ventricular wall thickness and mass, and impaired diastolic function among persons with NAFLD, which are known risk factors for the development of AF . In a recent large population‐based study of over 3000 black and white middle‐aged adults with CT‐diagnosed NAFLD, NAFLD was independently associated with subclinical myocardial remodelling and dysfunction independent of established heart failure risk factors .…”
Section: Discussionmentioning
confidence: 99%
“…41 A number of studies have reported increased left atrial volume and size, left ventricular wall thickness and mass, and impaired diastolic function among persons with NAFLD, which are known risk factors for the development of AF. [41][42][43] In a recent large population- (GGT), a marker of both hepatocyte injury and systemic oxidative stress, is independently associated with incident AF, whereas aminotransferases, as markers of hepatocyte injury alone, have not been independently associated with incident AF. 44 Fibrosis itself may play a significant role in the development of…”
Section: Ta B L E 2 Indications For Hospitalizationmentioning
confidence: 99%